Identifikasi Pencemaran Air Tanah terhadap Air Lindi Menggunakan Metode Geolistrik Konfigurasi Wenner Alpha: Studi Kasus TPS Institut Teknologi Sumatera - Mhd. Afido Ikhsan; Purwaditya Nugraha (Mataram University, 2026)
Suboptimal waste management has the potential to produce leachate that can pollute groundwater. This study aims to identify the presence, depth, and distribution of leachate around the Temporary Disposal Site (TPS) of the Sumatra Institute of Technology using the Wenner Alpha configuration geoelectric resistivity method with the Electrical Resistivity Tomography (ERT) approach. Data acquisition was carried out on several tracks with an electrode spacing of 5 m. The data were processed using Res2DInv software to obtain a two-dimensional resistivity cross-section. The results show a low resistivity zone (<10 Ωm) which is interpreted as an indication of leachate at shallow to medium depths, with a lateral distribution following local lithological conditions. These findings indicate the potential for groundwater pollution around the ITERA TPS. This study is expected to be the basis for environmental management and groundwater pollution mitigation.